Cuida e ser cuidado: compreendendo as significações desse processo para famíliares cuidadores e idosos dependentes usuários de um Centro Dia - Roque, Charles José [UNESP] (2014)
Brazil has more than 20 million elderly and most of them help their families,working and/or actively participatingin the society. It is estimated that the number of people aged 60 and over,must pass from 13.8% in 2020 to 33.7% in 2060.Aging is complexanda multi-determined process involving biological, psychological, social and cultural aspects. However it is pursuedallof themto experience aging with health, autonomy and independence, a portion of thispopulation lives inafragilecondition with physical and/or cognitive limitations. This is the main target audience of the Centro de Convivência para Idosos(CCI)2 in Botucatu, São Paulo, where this research was conducted. The CCIhas professionals who provide physical, cognitive stimulation and social activities for seniors and supportinggroups andguidance to carer family.The aim of this study was to investigate the process of caring dependent older people, attending theCentro Dia, trying to understand the meanings of this process fortheseniors and for carer family. In the first stage it was performed the characterization of 75 users using the medical records of the CCI. The results showed that 79% are women; 75% are between 70 and 89 years old; 40% havelow education; 67% are widowed and80%arewhite. Seniors from this Center became dependent as a result, mainlyof Alzheimer's disease (AD) and 35% of cerebrovascular accident (CVA) 25%. Regarding comorbidities, 63% have one ortwo of them, and 38%,three or more; 65% have threeor more disability in basic activities and 100% have three or more disability in instrumental activities of daily living; 100% use of polypharmacy; 61% is caredonly by theirfamily without outsidehelp. In the second stage,semi-structured interviews were conducted with four seniors and four carer families. The analysis occurred via meaning core, based mainly in workcategories and awareness of socio-historical psychology. It was found that the process of caring is largely ...